Optimizing in-store warehouse safety: A DEMATEL approach to comprehensive risk assessment - Sayed Vahid Esmaeili; Ali Alboghobeish; Hosein Yazdani; Aysa Ghasemi Koozekonan; Mostafa Pouyakian (PLoS ONE, 2025)
Introduction In-store warehouses can be a dangerous place due to the storage of a high volume of diverse life goods which may raise the total risk of warehouse. The turnover of goods in this kind of warehouse is very high. Therefore, safety risk is a multi-criteria problem and risk assessment of a such dynamic place needs an accurate and simple method to use. This study was conducted to design and validation of a method for risk assessment of in-store warehouses using the DEMATEL method. Materials & methods This cross-sectional descriptive analytical study was conducted between 2015 to 2016. First, a preliminary questionnaire was prepared by reviewing the available studies and documents. After assigning the group of experts and validating the questionnaire base on the content validity index (CVI) and content validity ratio (CVR), the weight of each of the parameters affecting the safety of the warehouse was determined. Then, the risk calculation model was developed. This model was validated using the failure modes and effects analysis (FMEA) method and Bland-Altman statistical method. Finally, to simplify the use of the developed risk assessment method, the algorithm of the model was also created. Results The results showed that 21 factors are among the main factors affecting the safety of the in-store warehouse, among which the "igniting and explosive property of the goods" factor had the most impact and the "warehouse working hours" factor had the least impact. The results achieved from the designed model were consistent with the FMEA method. Conclusion Based on the results, the newly designed risk assessment method can analyze the risks in the in-store warehouses faster and more accurately than the existing methods.